ISLAM DAN PEMBASMIAN KEMISKINAN BANDAR: Islam and the Erradication of Urban Poverty - Abdul Rahman, Muhamad Zulfadli; Mohamad, Mohammad Taqiuddin; Abdul Azzis, Muhammad Shamshinor (Jurnal Syariah, 2020)
Urbanisation has created a disparity between the standard of living in urban and rural areas. Subsequently, more and more people are migrating from the rural areas to the urban areas due to the lure of wider economic opportunities and greater access to infrastructure and facilities. Unfortunately, massive urban migration gradually limited economic opportunities for migrants, and this has led to wide-spread urban poverty. This article will explain the phenomenon of urban poverty and discuss urban poverty eradication from an Islamic perspective. This study employs the qualitative approach by applying the inductive, deductive and comparative content analysis method where the primary data are derived from library research, as well as from previous studies. The study found that the authority and community both play an important role in addressing urban poverty. This can be addressed through several measures of poverty eradication implemented in Islam, which include correcting belief about the economy, ensuring a balance wealth distribution from the rich to the poor, and changing attitudes and motivation at the ground level. In this regard, the authority should focus on creating a balanced distribution of wealth, facilitating a strategic economic management plan, adopting priority-based economies, effective implementation of poverty eradication policies, adoption of growth strategies, improving basic facilities and focusing on institutional roles.